تأثير جائحة كورونا على الأسرى الفلسطينيين في السجون الإسرائيلية - عقل, صلاح (جامعة الوادي.University eloued, 2022)
اولت هذه الدراسة انتشار مرض كوفيد 19 في أوساط الأسرى الفلسطينيين في السجون الإسرائيلية، ومماطلة إسرائيل في تطعيمهم عند توفر التطعيمات، حيث تتعمد إدارة مصلحة السجون حرمان الأسرى من أبسط الحقوق التي نصت عليها كافة المواثيق الدولية وفي مقدمتها حقهم في العلاج. فالاحتلال الإسرائيلي يهدف إلى معاقبة الأسرى الفلسطينيين على ممارستهم حقهم المشروع في المقاومة، من خلال عدد من الوسائل من بينها الإهمال الطبي، وفي ظل انتشار فيروس كورونا من خلال المماطلة أو التأخر في إعطائهم التطعيم لفيروس كورونا، مما زاد من معاناتهم وعرض حياتهم للخطر، ويعد عقوبة إضافية تفرضها سلطات الاحتلال عليهم. وتناولت الدراسة أيضًا موقف المنظمات الحقوقية والإنسانية الرافضة للقرار الإسرائيلي، ومدى تأثير الوباء على الأسرى وبالأخص المرضى وكبار السن منهم This study examined the spread of Covid-19 disease among Palestinian prisoners in Israeli prisons, and Israel's procrastination in vaccinating them when the vaccinations are available. Where the administration of the Prisons Authority intends to deprive prisoners of the most basic rights stipulated in all international conventions, foremost among which is their right to treatment. The Israeli occupation aims to punish Palestinian prisoners to exercise their legitimate right to resistance, through a number of means, including medical negligence, and in light of the spread of the Corona virus, the occupation punishes them by procrastinating or delaying giving them the Coronavirus vaccination, which increased their suffering and put their lives at risk, and it is an additional penalty imposed on them. The study also examined the position of human rights and humanitarian organizations rejecting the Israeli decision, and the extent of the impact of the epidemic on prisoners, especially the sick and the elderly
Keywords: أسرى؛ السجون الإسرائيلية؛ كورونا؛ التطعيم؛ هيئة شؤون الأسرى; Prisoners; Israeli prisons; Corona; vaccination; Prisoners Affairs Authority.